2018
DOI: 10.1002/anie.201803183
|View full text |Cite
|
Sign up to set email alerts
|

Two‐fold Bioorthogonal Derivatization by Different Formylglycine‐Generating Enzymes

Abstract: Formylglycine-generating enzymes are of increasing interest in the field of bioconjugation chemistry. They catalyze the site-specific oxidation of a cysteine residue to the aldehyde-containing amino acid C -formylglycine (FGly). This non-canonical residue can be generated within any desired target protein and can subsequently be used for bioorthogonal conjugation reactions. The prototypic formylglycine-generating enzyme (FGE) and the iron-sulfur protein AtsB display slight variations in their recognition seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 55 publications
(138 reference statements)
2
47
0
Order By: Relevance
“…Because AtsB proteins are predicted to contain three [4 Fe−4 S] 2+ ‐type clusters, a maximum of 12 Fe atoms per molecule can be expected . We observed that AtsB required additional N‐ and C‐terminal auxiliary sequences to efficiently convert cysteine within its endogenous substrate sequence in vitro (peptide P1 ) . Peptide P2 , which carries merely one additional amino acid residue on either end of the core motif, was not converted in detectable amounts by MM‐AtsB in a standard 5:1 substrate/enzyme ratio and an incubation time of 60 min at 37 °C in the presence of excess SAM under argon (Figure S2).…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…Because AtsB proteins are predicted to contain three [4 Fe−4 S] 2+ ‐type clusters, a maximum of 12 Fe atoms per molecule can be expected . We observed that AtsB required additional N‐ and C‐terminal auxiliary sequences to efficiently convert cysteine within its endogenous substrate sequence in vitro (peptide P1 ) . Peptide P2 , which carries merely one additional amino acid residue on either end of the core motif, was not converted in detectable amounts by MM‐AtsB in a standard 5:1 substrate/enzyme ratio and an incubation time of 60 min at 37 °C in the presence of excess SAM under argon (Figure S2).…”
Section: Methodsmentioning
confidence: 88%
“…As described in our previous study for MM‐AtsB, both enzymes were purified anaerobically and we were able to isolate KP‐AtsB and MM‐AtsB with an average iron content of 4.0±0.6 and 7.9±0.7 atoms per molecule, respectively (see the Supporting Information and Figure S1). Because AtsB proteins are predicted to contain three [4 Fe−4 S] 2+ ‐type clusters, a maximum of 12 Fe atoms per molecule can be expected .…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations